2012
DOI: 10.1016/j.fishres.2012.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Linking effort and fishing mortality in a mixed fisheries model: Comparing linear versus non-linear assumptions

Abstract: a b s t r a c tSince the implementation of the Common Fisheries Policy of the European Union in 1983, the management of EU fisheries has been enormously challenging. The abundance of many fish stocks has declined because too much fishing capacity has been utilised on healthy fish stocks. Today, this decline in fish stocks has led to overcapacity in many fisheries, leading to incentives for overfishing. Recent research has shown that the allocation of effort among fleets can play an important role in mitigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…15 SIMFISH Bartelings, Hamon, Berkenhagen, & Buisman, 2015Kempf et al, 2016. 16 FISHRENT IFRO Frost, Andersen, & Hoff, 2011, 2013Lassen, Anker Pedersen, Frost, & Hoff, 2013;Thøgersen et al, 2012;Salz et al, 2010. 17 FISHRENT TI Salz et al, 2011Simons, Bartelings, et al, 2014;Simons, Döring, & Temming, 2015a;Temming, 2015b.…”
Section: Stoch Hcr (Itq Wealth)mentioning
confidence: 99%
“…15 SIMFISH Bartelings, Hamon, Berkenhagen, & Buisman, 2015Kempf et al, 2016. 16 FISHRENT IFRO Frost, Andersen, & Hoff, 2011, 2013Lassen, Anker Pedersen, Frost, & Hoff, 2013;Thøgersen et al, 2012;Salz et al, 2010. 17 FISHRENT TI Salz et al, 2011Simons, Bartelings, et al, 2014;Simons, Döring, & Temming, 2015a;Temming, 2015b.…”
Section: Stoch Hcr (Itq Wealth)mentioning
confidence: 99%
“…The aim of this paper is to use applied economic modeling to evaluate the probable impacts of fish stock enhancement and pollution control on fish catches and livelihoods and highlight opportunities to enhance fish stock recovery plans and actions. Economic modeling has been applied widely in fisheries management science to: estimate the result of changes in fishing effort (Chae & Pascoe, ; Thogersen, Hoff, & Frost, ); assess the performance of fishing regulation and its effects on fisheries (Edwards, Hillary, Hoshino, Pearce, & Agnew, ; Holland & Herrera, ; Johnston, Arlinghaus, & Dieckmann, ; Marchal, Little, & Thebaud, ); analyze the economic effects of marine protected areas (Merino, Maynou, & Boncoeur, ); and evaluate the potential performance of stock enhancement programmes (Ye, Loneragan, Die, Watson, & Harch, ). Application of economic modeling to evaluate impacts of restocking and conservation measures on small‐scale fishers on inland waters constitutes a notable innovation, with the potential to contribute to achieving Aichi Target 6 by 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent experience shows that reductions in effort need not lead to the expected decrease in fishing mortality (ICES, 2013d;Kraak et al, 2013), equally implying that reductions in F can occur without reductions in effort (via, for instance, avoidance behaviours). Any deviations from the assumption that F is proportional to fishing effort will have implications for the management of fleets and realised management outcomes for the stocks Thógersen et al, 2012). Studies have shown that the relationship between fishing mortality and effort can be complex (e.g., Rijnsdorp et al, 2006;Thógersen et al, 2012;Ulrich et al, 2012) and influenced by such factors as the heterogeneous distribution of stocks and fleets (e.g., Rose and Kulka, 1999), targeting behaviour of fleets (Quirijns et al, 2008), interactions between vessels (Poos and Rijnsdorp, 2007), non-random behaviour of fishermen (Walters and Martell, 2004;Tidd, 2013) due to, for instance, changes in fuel costs or market value of the targeted stocks, and gear improvements (Arreguín-Sánchez, 1996).…”
Section: Introductionmentioning
confidence: 99%